Objective-C for absolute beginners : iPhone, iPad and Mac programming made easy - Kaczmarek, Stefan; Bennett, Gary; Lees, Brad; Fisher, Mitch (Apress, 2018)
Learn Objective-C and its latest release, and learn how to mix Swift with it. You have a great idea for an app, but how do you bring it to fruition? With Objective-C, the universal language of iPhone, iPad, and Mac apps. Using a hands-on approach, you'll learn how to think in programming terms, how to use Objective-C to construct program logic, and how to synthesize it all into working apps. Gary Bennett, an experienced app developer and trainer, will guide you on your journey to becoming a successful app developer. Along the way you'll discover the flexibility of Apple's developer tools If you're looking to take the first step towards App Store success, Objective-C for Absolute Beginners, Fourth Edition is the place to start. What You'll Learn Understand the fundamentals of computer programming: variables, design data structures, and working with file systems Examine the logic of object-oriented programming: how to use classes, objects, and methods Install Xcode and write programs in Objective-C Who This Book Is For Anyone who wants to learn to develop apps for the iPhone, iPad, Mac, or Watch using the Objective-C programming language. No previous programming experience is necessary.